Unexplained apnoea and loss of consciousness during sub arachnoid block for caesarean section - Acharya, SP; Marhatta, MN; Amatya, R (Kathmandu University Medical Journal, 2010)
Sub arachnoid block (SAB) is often perceived safe by many anesthesiologists and other faculties but is also not completely safe choice especially in pregnant females, as the incidence of complications and local anaesthetic agent toxicity is high in these groups of patients. Here we present four such cases out of the seventeen patients over a period of six months, who developed apnoea and transient loss of consciousness after spinal anesthesia for lower segment caesarean section. Typically all these patients after spinal anesthesia developed difficulty in breathing, became apnoea and had loss of consciousness for about a minute or two. The apnoea was relieved with bag and mask ventilation following which the patient regained consciousness and start breathing normally. The rest of the procedure was uneventful. We presented these cases with aim of sharing similar experiences, and to aware about the possibility of such events as these events do occur frequently but case reports and literatures are unavailable. Key words: Apnoea; loss of consciousness; lower segment caesarean section (LSCS); Sub arachnoid block (SAB). DOI: 10.3126/kumj.v7i4.2766 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 419-422